A Phase I/II study of the combination of lapatinib and oral vinorelbine in HER2-positive metastatic breast cancer. (5th January 2018) - Chen, Tom Wei-Wu; Yeh, Dah-Cherng; Chao, Tsu-Yi; Lin, Ching-Hung; Chow, Louis Wing-Cheong; Chang, Dwan-Ying; Hsieh, Yao-Yu; Huang, Shu-Min; Cheng, Ann-Lii; Lu, Yen-Shen; Consortium, Taiwan Breast Cancer
Abstract : In this Phase I/II study, combination of oral vinorelbine and lapatinib is tolerable and with some efficacy in HER2-positive metastatic breast cancer with some long-term responders. Abstract: Background: The combination of lapatinib and oral vinorelbine for HER2 positive metastatic breast cancer (MBC) is convenient but with uncertain toxicity profiles. A Phase I/II study was designed to understand the tolerability and efficacy of this combination treatment. Method: Female MBC patients with HER2 positive were eligible. Lapatinib was given once daily and oral vinorelbine was given on Days 1 and 8 of a 21-day cycle. A 3 + 3 standard dose–escalation rule was applied in the Phase I study. The primary endpoint of the Phase II study was PFS. In the Phase II part, because no DLT was observed in the first 20 patients, vinorelbine dose–escalation was permitted if no significant toxicities after the first cycle was observed. Result: From June 2009 to February 2013, 46 patients were enrolled in Phase I ( n = 15) and II ( n = 31) studies. Median age was 52.8 (range 34.3–84.0); 28 (60.9%) patients were ER positive. In the Phase I study, two patients had DLTs (neutropenia ( n = 2), diarrhea ( n = 1)). The MTD was determined at lapatinib 1000 mg plus oral vinorelbine 50 mg/m 2 . In the Phase II study, 11 patients safely had vinorelbine escalated to 60 mg/m 2 on cycle 2. The median PFS was 5.6 months (95% CI 5.2–5.9); 6 (19.4%) patients had PR; the clinical benefit rate was 38.7%. Six patients had disease control over 2 years. Conclusion: Lapatinib 1000 mg and oral vinorelbine 50 mg/m 2 were tolerable with manageable toxicities. Escalation to vinorelbine 60 mg/m 2 is feasible if no significant toxicities after the first cycle. Clinical efficacy was demonstrated with long-term responders observed.